(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
Microorganisms, like other living organisms, carry species-specific traits from generation to generation. But under the influence of the external environment, some kind of morphological and physiological properties can change. For example, Louis Pasteur artificially created irreversible changes in the causative agent of anthrax and developed vaccines to prevent these diseases. These and similar examples showed that microorganisms can change their properties depending on the living conditions.